Measurement of very low density and low density lipoprotein apolipoprotein (Apo) B-100 and high density lipoprotein Apo A-I production in human subjects using deuterated leucine. Effect of fasting and feeding. - Cohn, J S (1990)
Six normolipidemic male subjects, after an 8-h overnight fast, were given a bolus injection and then a 15-h constant intravenous infusion of [D3]L-leucine. Subjects were studied in the fasted state and on a second occasion in the fed state (small, physiological meals were given every hour for 15 h). Apolipoproteins were isolated by preparative gradient gel electrophoresis from plasma lipoproteins separated by sequential ultracentrifugation. Incorporation of [D3]L-leucine into apolipoproteins was monitored by negative ionization, gas chromatography-mass spectrometry. Production rates were determined by multiplying plasma apolipoprotein pool sizes by fractional production rates (calculated as the rate of isotopic enrichment [IE] of each protein as a fraction of IE achieved by VLDL (d less than 1.006 g/ml) apo B-100 at plateau. VLDL apo B-100 production was greater, and LDL (1.019 less than d less than 1.063 g/ml) apo B-100 production was less in the fed compared with the fasted state (9.9 +/- 1.7 vs. 6.4 +/- 1.7 mg/kg per d, P less than 0.01, and 8.9 +/- 1.2 vs. 13.1 +/- 1.2 mg/kg per d, P less than 0.05, respectively). No mean change was observed in high density lipoprotein apo A-I production. We conclude that: (a) this stable isotope, endogenous-labeling technique, for the first time allows for the in vivo measurement of apolipoprotein production in the fasted and fed state; and (b) since LDL apo B-100 production was greater than VLDL apo B-100 production in the fasted state, this study provides in vivo evidence that LDL apo B-100 can be produced independently of VLDL apo B-100 in normolipidemic subjects.